Upper-body vibration as part of warm-up: its effect on throwing velocity in elite adolescent handball players - Galazoulas, C.; Bassa, E.; Gaitanou, A.; Skoufas, D.; Karamousalidis, G. (Sport Sciences for Health, 2020)
Purpose: The purpose of this study was to examine the acute effects of 40-Hz upper-body vibration at two different amplitudes, added to the warm-up process, on throwing velocity in elite adolescent handball players. Methods: Seventeen elite male adolescent handball players (16.4 ± 0.7 years, mean ± SD) were exposed to two upper-body vibration protocols at 40 Hz (3 × 15 s), one with a 2-mm amplitude and one with a 4-mm amplitude, in a random crossover design. The athletes applied the standard pre-game warm-up, followed by three ball throws from a seated position. A radar gun was used to evaluate throwing velocity and the best shot was chosen. Then the vibration protocol was applied and, immediately afterwards, throwing velocity was retested. The two protocols were set 48 h apart. Results: Results revealed statistically significant improvement (p < 0.001) of throwing velocity after both vibration protocols. Conclusion: In conclusion, upper-body vibration at a frequency of 40 Hz and amplitude of either 2 mm or 4 mm may be considered as an addition to the regular warm-up in elite adolescent handball players, resulting in improved ball throwing velocity.